2016
DOI: 10.1118/1.4944870
|View full text |Cite
|
Sign up to set email alerts
|

Proton and light ion RBE for the induction of direct DNA double strand breaks

Abstract: The MC tool can predict SSB and DSB yields for light ions of various LET and estimate RBEDSB (direct). In addition, it can calculate the frequencies of different DNA lesion sizes, which is of interest in the context of biologically relevant absolute dosimetry of particle beams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Trends in SSB yields due to direct and indirect effects were also comparable, with ~10% higher absolute values, whereas the reported ~5% higher yields for alphas due to indirect effects has not been obtained in our study. Another recent modelling study on ion induced direct DNA damage67 revealed for protons with increasing LET (up to 30 keV/μm) a linear decrease of SSB yields and linear increase of DSB yields; for a constant LET value of 24 keV/μm, the SSB yields increased and the DSB yields decreased for He, Li and C with increasing atomic number. The present results on direct DSB yields show the same trends at about 20% lower yields, whereas the about 20% lower direct SSB yields exhibit no clear trend with atomic number and no linear decrease with increasing LET.…”
Section: Discussionmentioning
confidence: 97%
“…Trends in SSB yields due to direct and indirect effects were also comparable, with ~10% higher absolute values, whereas the reported ~5% higher yields for alphas due to indirect effects has not been obtained in our study. Another recent modelling study on ion induced direct DNA damage67 revealed for protons with increasing LET (up to 30 keV/μm) a linear decrease of SSB yields and linear increase of DSB yields; for a constant LET value of 24 keV/μm, the SSB yields increased and the DSB yields decreased for He, Li and C with increasing atomic number. The present results on direct DSB yields show the same trends at about 20% lower yields, whereas the about 20% lower direct SSB yields exhibit no clear trend with atomic number and no linear decrease with increasing LET.…”
Section: Discussionmentioning
confidence: 97%
“…Monte Carlo simulations of radiation-induced DNA damage are, in effect, the modeled embodiment of what we know-or believe we know-from the analysis of a large number of published studies on the induction of DNA damage by ionizing radiation. Monte Carlo simulations are also useful for the generation and testing of hypothesized mechanisms of action [9][10][11][12][13], for developing quantitative algorithms for the classification of clusters of DNA lesions as DSB and non-DSB clusters [1,[14][15][16][17], and for the analysis of measured fragment-size distributions [15,18,19]. The fundamental radiobiologic and clinical significance of particle relative biological effectiveness (RBE) for the end point of DNA damage is reviewed in relation to the RBE for mutagenesis, chromosome aberrations, and reproductive cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…A pre-calculated nanodosimetric database with high precise has been published by Ramos et al 42 It consists of nanodosimetric quantities (M 1 ; M C 2 1 ; F 2 ; F C 2 3 ) defined in a cylinder target volume of 2.3 nm diameter and 3.4 nm length corresponding to a DNA segment of 10 base pairs of monoenergetic fully ionized charged particles (proton, 4 He, 7 Li, 9 Be, 11 B, 12 C, 14 N, 16 O) with energies ranging from 1 MeV/u to 1000 MeV/u. The data were simulated with TOPAS-nBio 43,44 extension of the TOPAS simulation software, 45 layered on the top of Geant4DNA 31,46 (version 10.2.p02).…”
Section: Pre-calculated Nanodosimetric Databasementioning
confidence: 99%
“…However, more and more findings have shown that the initial radiation damage to cells is closely related to the ionization cluster size generated by charged particles on the DNA scale. [12][13][14][15][16] Therefore, a more suitable tool for track structure description may be nanodosimetry. 17 In nanodosimetry, [18][19][20][21][22][23][24][25] the track structure of charged particles is characterized by the frequency distributions of the ionization cluster size (ICS), that is, the number of ionizations produced within a target volume in nanoscale.…”
Section: Introductionmentioning
confidence: 99%